2009
DOI: 10.2203/dose-response.08-025.nascarella
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Hormesis in Anticancer-Agent Dose-Responses

Abstract: ᮀ Quantitative features of dose responses were analyzed for 2,189 candidate anticancer agents in 13 strains of yeast (Saccharomyces cerevisiae). The agents represent a diverse class of chemical compounds including mustards, other alkylating agents, and antimetabolites, inter alia. Previous analyses have shown that the responses below the toxic threshold were stimulatory and poorly predicted by a threshold dose-response model, while better explained by a hormetic dose-response model. We determined the quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Additive, synergistic or antagonistic mutual interactions of two drugs can be quantified within the quasilinear region of the dose-effect-curves using the median effect principle of Chou [24] or the unified response surface area of Greco et al [25] . However the interactions of drug combination is difficult to quantify for hormetic dose-response-relations [26] . There are various models to assess hormesis for a single drug treatment [27] , [28] .…”
Section: Resultsmentioning
confidence: 99%
“…Additive, synergistic or antagonistic mutual interactions of two drugs can be quantified within the quasilinear region of the dose-effect-curves using the median effect principle of Chou [24] or the unified response surface area of Greco et al [25] . However the interactions of drug combination is difficult to quantify for hormetic dose-response-relations [26] . There are various models to assess hormesis for a single drug treatment [27] , [28] .…”
Section: Resultsmentioning
confidence: 99%
“…A marked increase in microvessel formation at lower doses between 0.625-1.25 µM was also observed. This bell-shaped effect (hormesis) is common in anticancer agents (15,42) which suggests the importance of maintaining the SFN at high concentrations (>5 µM) for cancer chemoprevention or treatment. These tube formation results were consistent with the cell viability data that showed that SFN inhibited the growth of ECs at concentrations of 5-20 µM while at low concentrations of 0.625-2.5 µM, SFN promoted cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…However, in another context, these compounds may be of use as anticancer agents instead. Notably, however, they display the phenomenon of 'hormesis', a term widely used by toxicologists to describe a biphasic dose response to a drug, with stimulatory effects at low dose and inhibition at higher doses; thought to be an adaptive compensatory response to initial disruption of cellular homeostasis (31,32). At low doses a drug could block an endogenous inhibitory factor, resulting in stimulation, before it starts to exert its own inhibitory effect on other pathways at higher concentration.…”
Section: Discussionmentioning
confidence: 99%